Are there Multiple Bubbles in the Stock Markets? Further Evidence from Selected Countries - Zeren, Feyyaz; Yilanci, Veli (Ekonomika, 2019)
[full article and abstract in English]In this study, the existence of multiple bubbles in 15 selected countries is researched by means of the GSADF unit root test developed by Phillips, Shi, and Yu (2015). The data set consists of a weighted average of the monthly price/earnings ratios with the different start dates for countries whose data could accessed. As a result of the conducted analysis, the existence of multiple bubbles was detected for all the countries examined. The results demonstrate that bubbles in stock markets occur before the local and global crisis periods. We therefore conclude that the GSADF method may be used as one of the early warning systems of a financial crisis. It is significant for policymakers and investors to know these signs in terms of financial stability and profitable investments.
Keywords: Multiple Bubbles; Price / Earnings Ratio; Financial Crisis; GSADF Unit Root